Errata to Algebraic points on Shimura curves of Γ 0 ( p )-type (J. reine angew. Math., DOI 10.1515/crelle-2012-0068) - Keisuke Arai; Fumiyuki Momose (Journal für die reine und angewandte Mathematik (Crelles Journal), 2014)
Abstract. This is an erratum to http://dx.doi.org/10.1515/crelle-2012-0068 .